Case Report: A rare case of hepatoid carcinoma of the ovary with genomic profiling and long-term follow-up: diagnostic and therapeutic perspectives - Zuo, Yufang; Liu, Xuan; Pang, Yajun; Chen, Xiaowen; Li, Xiaofang; Gao, Jiangsheng; Liu, Bingjie; Liao, Sihai; Zhang, Ying; Guan, Chengnong (Frontiers in Oncology, 2025)
Hepatoid carcinoma of the ovary (HCO) is a highly uncommon and aggressive neoplasm originating from the surface epithelial cells of the ovary, characterized by hepatocyte-like differentiation. To date, most information on HCO is derived from case reports, with fewer than 50 documented cases globally. In this case report, we present a detailed account of the diagnosis, treatment, and prognosis of a patient diagnosed as having bilateral HCO, which is even rarer. Targeted next-generation sequencing revealed somatic mutations in PIK3C3 and TP53, with no BRCA1/2 alterations, and a molecular profile consistent with microsatellite stability and low tumor mutational burden. We also review the current literature to situate our findings within the broader context of existing knowledge. Given the rarity of bilateral HCO, our objective is to contribute to the existing body of knowledge by providing a comprehensive description of its clinical features, molecular characteristics, and treatment strategies. This effort may enhance understanding of this rare malignancy and offer insights to improve patient outcomes in clinical practice.